Challenges And Needs In Integrating Sustainable Development Goals (Sdgs) Into High School Physics Curriculum: A Study In Lhokseumawe, Indonesia - Widya (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
This study examines the challenges and needs faced by high school physics teachers in Lhokseumawe, Indonesia, regarding the integration of Sustainable Development Goals (SDGs) into their curriculum. A cross-sectional survey using a Likert-scale questionnaire was administered to 11 physics teachers to gather data on key barriers such as time constraints, availability of teaching materials, teachers’ understanding of SDGs, facility needs, training requirements, and school policy support. The results reveal that time constraints are perceived as a moderate barrier, with 36.36% of teachers reporting occasional difficulty in managing both the physics curriculum and SDG integration. A significant challenge is the limited availability of teaching materials related to SDGs, as 45.45% of teachers indicated a lack of resources to effectively teach these topics. Teachers also expressed a moderate level of difficulty in understanding SDGs, with 36.36% identifying this as a challenge in their teaching. The study highlighted the strong need for training on SDG concepts, with 45.45% of teachers strongly agreeing on the importance of professional development. Adequate facilities for teaching SDGs were less of an issue, as 36.36% of teachers reported that sufficient facilities were available. Finally, while some school policy support exists, 36.36% of teachers noted that policy alignment with SDG integration is still insufficient. These findings emphasize the need for targeted professional development programs, better teaching resources, and stronger policy support to facilitate the integration of SDGs in high school physics education.